Impacts on trust and social capital of a youth employment program in Yemen: Evaluation of the rural and urban advocates working for development intervention for the Social Fund for Development - Bertelli, Olivia; Kurdi, Sikandra; Mahmoud, Mai; Al-Maweri, Mohamad; Al Bass, Tareq (International Food Policy Research Institute, 2019)
This paper evaluates the impacts on the participants of the Yemen Social Fund for Development’s youth employment and training program called Rural and Urban Advocates Working for Development (RUAWFD). The evaluation used both traditional surveys and an innovative experimental game methodology to show that the employment program, in addition to aiding youth individually, has important benefits for the country as a whole by contributing to stronger social capital. The survey analysis finds for the program participants significant increases between the baseline and follow-up surveys in self-reported trust in local government institutions and officials, political parties, and tribes. In reflecting on the level of cooperativeness in their own communities, participants reported increased awareness of the presence of marginalized groups and increased perception of cooperativeness in surrounding communities. There was also a significant increase in self-reported trust in people generally, especially for trust in other young people and in people from other areas of Yemen. The experimental game methodology uses a common pool game from the experimental economics literature incentivized by cash payments to measure trust levels between pairs of RUAWFD participants from different geographic regions. This approach confirms the findings from the survey analysis while avoiding possible self-reporting bias. The game results show that trust was lowest at baseline for partners in which one of the partners was from one of the Northern governorates and the other was from one of the Southern governorates. After the intervention, however, not only were average trust levels higher, but Northern-Southern pairs of RUAWFD participants had trust levels closer to those for pairs from the same regions. These findings are consistent with the literature on inter-group contact theory suggesting that community interventions can increase trust in individuals and institutions. This research contributes to a growing literature on trust and social capital as important development indicators, particularly in relation to conflict. The main results suggest that reinforcing social ties across regions in Yemen is an important benefit of the Social Fund for Development’s role as a national development agency and an achievable objective to consider in planning development interventions to contribute to future post-conflict reconstruction.